Overview of gender mandates in Spanish-speaking children and youth: A systematic review - Hernández-Tique, Pamela del Carmen; Córdova-Hernández, Juan Antonio; Castellanos-Suarez, Viviana (Horizonte Sanitario, 2024)
Objective: To learn about the panorama of children, adolescents and young people of the Hispanic population regarding traditional gender mandates through scientific literature.Materials and methods: A systematic review derived from a qualitative analysis of the scientific literature on gender mandates, stereotypes, roles and sociocultural representations in children and adolescents was carried out; the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement in its recent version 2020 was used for the writing. For the search of scientific evidence, known databases were used; only articles published in nationally and internationally indexed journals were considered. The DeSC Thesaurus was used to identify keywords.Results: The quality of the report was evaluated with the PRISMA guideline and the methodological quality with the AMSTAR-2 check-list, resulting in a total of 13 articles. Subsequently, we proceeded to review the articles identified by means of the ICrESAI and IMeCI instruments to evaluate the usefulness of the studies, resulting in a total of 10 articles.Conclusions: From the analysis, it was concluded that hegemonic gender roles and stereotypes are still present in the individual and/or collective behaviors and discourses of the population, including BGT and youth. However, there is a tendency for the Spanish-speaking child, adolescent and youth population to change towards alternative concepts and ways of being men and women. Keywords: Gender; Childhood; Youth.